(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The article outlines the main features of the use of the theory of indefinite bundles in the evaluation of the cost-effectiveness of investment projects. He analysis of methods for quantifying the effectiveness of the IP under uncertainty suggests that the existing methods either eliminate the uncertainty from the IP model, which is inappropriate, since uncertainty is an integral characteristic of any forecast, or are unable to formally describe, and take into account all possible varieties of types of uncertainty. Methods based on the theory of fuzzy sets refer to the methods of evaluation and decision-making under conditions of uncertainty. Their use implies the formalization of the initial parameters and performance targets of the IP in the form of a vector of interval values (fuzzy interval), the hit in each interval of which is characterized by a certain degree of uncertainty. Also, the fuzzy-interval approach has advantages in solving the problems of forming an optimal portfolio of investment projects. To solve the problem of forming an optimal IP portfolio, a large number of models for the formation of an optimal IP portfolio have been developed, differing from each other in the form of objective functions, variable properties, used by mathematical methods, and uncertainty.